Transcendental Empirism: between Husserl and Derrida - Depraz, Natalie (Problemos, 2003)
The article demonstrates that the conceptíon of phenomenology as transcendental empiricism transforms the philosopical paradigm leading from the herme- neutics to pragmatics. From this standpoint, the method of cooperation between the empiricity and transcendentality in the constitution of the primordiality equatcs Husserlian method to the Derrida’s method of primordial contamination. Husserl and Derrida are in the same field of the shored critical choices; they both reject dualism, monism, dialectics, and her- meneutics. In short, transcendental empiricism implies an oxymoronic, codynamic method that is legimated by the primordial tension which is characteristic for the vcry development of the primordializing of primordiality.